Age and gender differences in the recognition, use and perception of a selection of Anglicisms - Carlos Ponce Folgado (Estudios de Lingüística)
It is undeniable that, in recent years, the English language has had a considerable and growing impact on the language and culture of Spain. The present research aims to explore and examine the knowledge, use and perception of a specific selection of Anglicisms, taking into consideration age and gender variables, in a group of one hundred randomly chosen native Spanish individuals. Firstly, a theoretical framework that defines the concept of Anglicism, is presented emphasising its pragmatic functions, in order to understand the purpose behind their use and the general population’s perception of them. The influence of English on Spanish society throughout history is also addressed, along with potential factors that have contributed to the increase of English terms in the Spanish vocabulary. For the implementation of this study, a survey was designed and distributed online targeting one hundred individuals. The first part of the survey included questions about personal traits: age within a suggested range, gender, highest level of education, and English proficiency level. On the other hand, the second part focused on answering questions about a selection of eight Anglicisms with the aim of gathering relevant information. These eight terms were grouped into four categories: curvy and outfit for fashion; gadget and streaming for technology; bagel and detox for gastronomy; and finally, red flag and staff for society. In this way, the aim was to determine the frequency, context and reasons for the use of these terms, as well as the opinions they elicit, taking into account potential age and gender differences. The main findings reveal that young people, for the most part, show a largely positive attitude towards Anglicisms, preferring to use them primarily in oral and informal contexts. Additionally, significant differences were observed between genders in the familiarity with certain Anglicisms, and it was found that context influences and plays an important role in their knowledge and use. Therefore, the findings obtained in this study can be useful for future research on Anglicisms and for broadening the understanding of this current phenomenon.